Effect of hydroxyapatite and bovine serum albumin on the antibacterial activity of MTA - Mohammadi, Zahed; Shalavi, Sousan (Iranian Endodontic Journal, 2011)
INTRODUCTION: The purpose of this study was to compare the inhibitory effect of bovine serum albumin (BSA) and hydroxyapatite (HA) on the antibacterial activity of white-colored MTA (WMTA) against Staphylococcus (S.) aureus and Streptococcus (S.) mutans after 24 and 72 hours. MATERIALS & METHODS: All materials were prepared according to the manufacturer’s directions immediately before testing. The antibacterial effect of each group (WMTA, WMTA+BSA and WMTA+HA) was determined by measuring the diameter of zone of inhibition in millimeters after incubation at 37°C for 24 and 72 hours in a humid atmosphere. Each test was repeated three times. Data were analyzed using ANOVA and Tukey’s test. RESULTS: In the 24 hours samples as well as in 72 hours samples, the antibacterial activity of MTA+HA group was significantly greater than two other groups against S. aureus (P < 0.05). However, the antibacterial activity of MTA+HA group against S. mutans was not significantly different from the MTA group in 24 hours as well as 72 hours samples. BSA reduced the antibacterial activity of MTA against both tested bacteria in the 24 and 72 hour samples (P < 0.05). CONCLUSION: The products studied exhibited antibacterial activity. However, in both time intervals, the MTA+HA group exerted the greatest activity against S. mutans and S. aureus.